Emergence of Institutional Islamophobia: The Case of the Charity Commission of England and Wales - Ismail Patel (ReOrient, 2017)
The Charity Commission of England and Wales supports and regulates the charity sector whose emergence can be traced back to the early seventeenth century. However, there has been limited academic scrutiny of its regulatory approach particularly regarding Muslim-identified charities. This article first challenges the Commission's claim to be an independent body, and second questions whether its contemporary role reveals institutional Islamophobia. It is argued that, since partnering with the UK government's “Prevent” agenda – or war on terror – to control ungoverned spaces for extremism, the Commission has assumed a policing role. This role is analysed through discourse theory and a Foucauldian approach to disciplinary techniques. To analyse the repertoire of institutionalised Islamophobia, the study draws upon Carmichael and Hamilton's definition of institutional racism, the Parekh Report , and Pilkington's ten components of institutional racism. In challenging the Commission's claim to independence, the article highlights the changes in its practices and structure. It argues the structural changes have deflected accountabilities of the board members and chair and resulted in the politicisation of their selection process. Furthermore, the shifts in the Commission's practices have had a disproportionate impact on Muslim charities, where thirty-eight per cent of all disclosed statutory investigations conducted are on Muslim charities despite representing only 1.21 per cent of the sector. This article provides a discourse analysis of the regulatory approach of a significant public body and departs from investigations of subjective and media representations of Muslims that have monopolised research on Islamophobia.